Analisis kualitas pelayanan dan pengalaman pelanggan dalam meningkatkan kepuasan pelanggan pada usaha mikro Pure Water - Lomboan, Richiko Hoinkel; Wibowo, Yudi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aimed to analyze strategies for improving service quality based on customer experience to enhance consumer satisfaction in micro businesses of drinking water refill services, specifically at Depot Air Pure Water in Bogor Regency. The research was motivated by the critical role of service quality and customer experience in shaping satisfaction and loyalty, especially in micro-business sectors. A descriptive qualitative approach was employed, with data collected through in-depth interviews, direct observations, and literature review. The results indicated that service dimensions such as service speed, staff friendliness, facility cleanliness, and environmental comfort significantly influenced customers’ emotional and cognitive experiences. Based on these findings, the recommended service improvement strategies included deep understanding of customer needs, staff training in empathetic service delivery, and physical facility enhancements to support comfort. This study provided practical contributions for micro business actors in designing customer experience-oriented service strategies, as well as theoretical contributions to the management of service literature in the micro-business sector.